Influence of an individual anthropometric profile on the physical fitness of students in the conditions of the far north - T.E. Kopeykina; A.V. Bykov; M.P. Anisimov; A.A. Lenin (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the characteristics of physical fitness of students, taking into account the individual anthropometric profile according to the principles of the Quetelet mass-height index as an indicator of adaptation to the natural and climatic factors of the Far North. Methods and structure of the study. Scientific work was carried out from September 2022 to December 2022 at the Institute of Shipbuilding and Marine Arctic Technology (Sevmashvtuz), a branch of Northern (Arctic) Federal University in Severodvinsk. 3rd year students, men (n=88), aged 21±1 years, took part. All students were engaged in applied physical culture for two years. Results and conclusions. The conducted experiment indicates that the indicators of the individual anthropometric profile of students according to the principles of the Quetelet mass-height index were distributed over all variations of this test, their assessment is due to adaptation to the conditions of the Far North. The group of students with a good index showed higher results in all physical fitness tests. The impact of environmental factors did not affect the performance of students in this group. The ratio of parameters in the flexibility test changed in favor of the group with exhaustion, poor index. Thus, the adaptation of the body to environmental conditions is not the same.